The Indo-Pacific axis peace and prosperity or conflict? - Chandra, Satish; Ghoshal, Baladas (Routledge, Taylor & Francis Group, 2018)
The term 'Indo-Pacific' is being used increasingly in the global strategic/geo-political discourse in recent years. The rise of China as an economic giant and a rising military power has led to the consequent shift of international politics and relations to Asia as the fulcrum. It also poses the question, whether the Indo-Pacific region will become a theatre of tension and instability, or a contributor to peace and prosperity for the larger populations that reside herein.